Rhetoric and Scripture in Augustine's Homiletic Strategy : Tracing the Narrative of Christian Maturation - Glowasky, Michael (Vigiliae Christianae, Supplements, 2021)
In Rhetoric and Scripture in Augustine's Homiletic Strategy , Michael Glowasky offers an account of how Augustine's pastoral concerns shape the rhetorical strategy in his Sermones ad populum . While it has been widely recognized that Augustine draws on classical rhetoric in his sermons, how his use of rhetoric in his Sermones relates to his pastoral theology has yet to be addressed. Through careful examination of Augustine's preaching practice, this book provides the most comprehensive account of Augustine's homiletic strategy in his Sermones to date. As such, it helps us better appreciate the value of the Sermones ad populum as a work in its own right, while at the same time advancing our understanding of Augustine as a preacher, teacher, and pastor.